The influence of social media marketing on purchase intention with customer engagement as mediator - Adinda, Chery; Listiana, Erna; Barkah, Barkah; Fitriana, Ana (Institute of Computer Science (IOCS), 2025)
In the modern era, digital technology simplifies life, particularly through gadgets and social media. Social media enables users to watch videos, promote products, and create content, benefiting individuals and brands alike. This analysis purpose to identify the influence of surveillance, sharing of information, social interaction, attraction on social media, and consumer engagement as mediating variables on purchase intention for the @makeoverid account on Instagram. The study applies quantitative methods and collects primary data that meet specific criteria. Data collection techniques by utilizing questionnaires online via Google Form and utilizing scale of Likert (1-5). Structural Equation Modeling (SEM) is utilizied as adata measurement technique using SMARTPLS 4.0 statistical application helping. The population of this study includes Instagram users, both male and female, over 17 years old, who are familiar with Make Over products through the @makeoverid account. A sample of 200 respondents was required to meet SEM analysis requirements. The research additionally intends examine the causal links between variables, offering a comprehensive perpective on the factors that influence consumer behavior within a social media marketing context. The research results show that not all tested factors significantly impact consumer engagement. Surveillance does not affect customer engagement, while information sharing, social interaction, and attraction do. Additionally, customer engagement significantly influences purchase intention. Indirectly, information sharing, social interaction, and attraction positively impact purchase intention through consumer engagement, while surveillance does not.